New and Little-Known Eurasian Dithrycini (Diptera, Tephritidae) - Korneyev, V.A. (Вестник зоологии, 2002)
Oedaspis schachti sp. n. from Taiwan is described; it fits near Oe. pibari (Kwon), Oe. wolongata (Wang) and Oe. fini Freidberg, differing in details of wing pattern. Oe. fissa Loew, 1862 is the senior synonym of Oe. latifasciata Hering, 1937, syn. n. Oe. ragdai Hering is recorded for the first time from Tajikistan and Iran, Oe. dichotoma from Kyrghyzia and Turkmenistan, and Oe. fissa from North Africa. Ptiloedaspis tavaresiana Bezzi and Dithryca guttulosa (Loew) previously known from descriptions, are figured. Keys to Palaearctic and Asian species of Oedaspis Loew and Dithryca Rondani are compiled. Описан Oedaspis schachti sp. n. с Тайваня; вид близок Oe. pibari (Kwon), Oe. wolongata (Wang) и Oe. fini Freidberg, отличаясь деталями крылового рисунка. Oe. fissa Loew, 1862 — старший синоним Oe. latifasciata Hering, 1937, syn. n. Oe. ragdai Hering указан впервые из Таджикистана и Ирана, Oe. dichotoma — из Киргизии и Туркменистана, а Oe. fissa — из Северной Африки. Приведены рисунки Ptiloedaspis tavaresiana Bezzi и Dithryca guttulosa (Loew), ранее известных по описаниям. Составлены таблицы для определения евразиатских видов родов Oedaspis Loew и Dithryca Rondani.